2016
DOI: 10.1038/ncomms13046
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of carbon release from the active layer and permafrost deposits on the Tibetan Plateau

Abstract: The sign and magnitude of permafrost carbon (C)-climate feedback are highly uncertain due to the limited understanding of the decomposability of thawing permafrost and relevant mechanistic controls over C release. Here, by combining aerobic incubation with biomarker analysis and a three-pool model, we reveal that C quality (represented by a higher amount of fast cycling C but a lower amount of recalcitrant C compounds) and normalized CO 2 -C release in permafrost deposits were similar or even higher than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 69 publications
3
107
0
1
Order By: Relevance
“…A path analysis was conducted to determine the factors responsible for the potential methane emissions (Figure a). Taking into account the relevance of environmental factors, PCA was conducted to create a multivariate functional index for the physicochemical factors of soil nutrients, which were all significantly correlated (Supporting Information Table S4) (Chen et al., ). Principal component 1 (PC1), which explained 97.61% of the total variance (Supporting Information Table S5), was then introduced as the index of soil nutrients into the path analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A path analysis was conducted to determine the factors responsible for the potential methane emissions (Figure a). Taking into account the relevance of environmental factors, PCA was conducted to create a multivariate functional index for the physicochemical factors of soil nutrients, which were all significantly correlated (Supporting Information Table S4) (Chen et al., ). Principal component 1 (PC1), which explained 97.61% of the total variance (Supporting Information Table S5), was then introduced as the index of soil nutrients into the path analysis.…”
Section: Resultsmentioning
confidence: 99%
“…An independent‐samples t ‐test was conducted to test the significance of the difference, and Pearson correlation coefficients were used to calculate the correlation in the PASW Statistics 18 (IBM, USA). Path analysis was conducted to analysis the effects of biotic and abiotic parameters on the methane emissions with using Amos 24 (IBM, USA) software (Chen et al., ). Before constructing a priori model of the path analysis, correlation analysis among all parameters were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Because the variables of climate, soil nutrient and soil environment groups were closely correlated, a principal components analysis (PCA) was performed to create a multivariate index representing each group (e.g. Chen, Li, et al., ; Chen, Liang, et al., ). Within each group, only variables significantly correlated with C turnover times were included in the PCA.…”
Section: Methodsmentioning
confidence: 99%
“…A central topic in previous studies on soil organic C (SOC) dynamics is SOC turnover time (τ soil ) and its determinants (Heckman et al., ; Koven et al., ; Schimel et al., ). It has been documented that at a small spatial scale, soil C turnover is mainly dependent on soil temperature and moisture (Craine, Fierer, & McLauchlan, ; Davidson & Janssens, ; Thomsen, Schjønning, Jensen, Kirstensen, & Christensen, ), soil chemical properties (Schindlbacher et al., ; Xu, He, & Yu, ; Xu, Shi, et al., ), C quality (Chen, Liang, et al., ) or soil microbial community (Chen, Li, Lan, Hu, & Bai, ; Cleveland, Nemergut, Schmidt, & Townsend, ), while at national and global scales, latitude, altitude and associated climatic variables are suggested to be responsible for the variability of τ soil (Chen, Huang, Zou, & Shi, ). Moreover, soil C turnover is also affected by natural (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the total potential soil CO 2 emission on the QTP ranges from 737.90–4224.77 g CO 2 m −1 y −1 , and thawing‐induced CO 2 emissions from permafrost soils would increase general soil respiration by at least about one third on average at a temperature of 5°C (Bosch et al, ). A laboratory incubation experiment indicated that the soils from the AL and PL on the QTP had similar CO 2 ‐emitting potentials (Chen et al, ), while another study suggested that control (nonexposed) soils had significantly higher CO 2 production rates than drape (exposed) soils in a permafrost collapse area on the northern QTP (Mu et al, ). Nevertheless, the abundant carbon stock (~29.6 ± 4.2%; Mu et al, ) was lost during the permafrost thaw and collapse processes, potentially from mineralization, leaching, photodegradation, and lateral displacement.…”
Section: Introductionmentioning
confidence: 99%